Diffusion of Social Information in Non-grouping Animals - Tóth, Zoltán; Jaloveczki, Boglárka; Tarján, Gergely (Frontiers in Ecology and Evolution, 2020)
Recent findings indicate that the utilization of social information, produced inadvertently by other individuals through their interaction with the environment, may be ubiquitous in the animal kingdom and social information-mediated effects on population growth and interspecies interactions are more prevalent than previously thought. However, we know little about how social information may spread among individuals when social cohesion among group-mates does not facilitate information diffusion, e.g. are there any perception-related, temporal and/or spatial parameters that may facilitate or limit its spread in temporary aggregations or among dispersed individuals in a population. In this work, we argued that living in cohesive groups is not necessarily required for the diffusion of social information and for social information-mediated effects to emerge in a population. We proposed that while learning complex problem-solving techniques socially is less likely to occur in non-grouping animals, the spread of adaptive responses to social stimuli, especially to non-visual cues, can be common and may affect population and/or community dynamics in a wide range of taxa. We also argued that network-based diffusion analysis could be a suitable analytical method for studying information diffusion in future investigations, providing comparable estimations of social effects on information spread to previous studies on group-living animals. We concluded that more studies are warranted if we are to better understand the role of social diffusion in animal populations and how species’ social and ecological characteristics are related to the underlying mechanisms of information spread in natural communities.